Controlling the Actuation Rate of Low‐Density Shape‐Memory Polymer Foams in Water. Issue 11 (9th October 2012) - Singhal, Pooja; Boyle, Anthony; Brooks, Marilyn L.; Infanger, Stephen; Letts, Steve; Small, Ward; Maitland, Duncan J.; Wilson, Thomas S.; Lendlein, Andreas
Abstract SMPs have been shown to actuate below their dry glass transition temperatures in the presence of moisture due to plasticization. This behavior has been proposed as a self‐actuating mechanism of SMPs in water/physiological media. However, control over the SMP actuation rate, a critical factor for in vivo transcatheter device delivery applications, has not been previously reported. Here, a series of polyurethane SMPs with systematically varied hydrophobicity is described that permits control of the time for their complete shape recovery in water from under 2 min to more than 24 h. This control over the SMP actuation rate can potentially provide significant improvement in their delivery under conditions, which may expose them to high‐moisture environments prior to actuation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>